2010
DOI: 10.1007/s10562-010-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure Sulfidation on the Structure of Sulfide Sites of Hydrotreatment Catalysts

Abstract: The effect of high-pressure sulfidation on (Co)Mo/Al 2 O 3 catalysts was studied by means of IR spectroscopy of adsorbed CO and thiophene hydrodesulfurization (HDS). A new IR cell, called CellEx, was designed in order to characterize catalysts sulfided in situ under H 2 S/H 2 flow with pressure varying from 0.1 up to 4.0 MPa. On Mo/Al 2 O 3 , high sulfidation pressure changes neither the HDS rate nor the MoS 2 site concentration. Conversely on CoMo catalyst, sulfidation under high pressure leads to a marked in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This cell allows obtaining similar sulfidation procedure for both IR characterizations and catalytic tests. 120 Another significant example can be mentioned in the case of the NO x selective reduction by hydrocarbons on oxide-based catalysts. Working on Ag/Al 2 O 3 samples for NO x reduction by ethanol, we observed the formation of cyanide and isocyanate species.…”
Section: Correlation Between Probe Studies and Activitymentioning
confidence: 99%
“…This cell allows obtaining similar sulfidation procedure for both IR characterizations and catalytic tests. 120 Another significant example can be mentioned in the case of the NO x selective reduction by hydrocarbons on oxide-based catalysts. Working on Ag/Al 2 O 3 samples for NO x reduction by ethanol, we observed the formation of cyanide and isocyanate species.…”
Section: Correlation Between Probe Studies and Activitymentioning
confidence: 99%
“…However, a previous study reported the effect of gas phase sulfidation pressure [10]: CO/IR did not detect a strong shift of the m CO/ CoMoS band but rather an increase of its intensity as pressure increased; no significant modification of the TOF for thiophene HDS was evidenced. Therefore, the effect of the liquid phase sulfidation on the CoMoS site nature is unlikely related to an increase of sulfidation pressure.…”
Section: Pressure Of Sulfidationmentioning
confidence: 65%
“…In previous studies on promoted catalysts sulfided in the gas phase, the thiophene HDS activity was reported to increase linearly with CoMoS site concentration, the latter measured by CO/IR [10,43,45,46]. In the case of liquid (Table 2) whereas the sulfide CoMoS site concentration decreases (Table 3).…”
Section: Effect Of Liquid Phase Sulfidation On Sulfide Sitesmentioning
confidence: 85%
See 1 more Smart Citation
“…All these groups work actively to the development of reactor‐cells for getting closer to industrial reaction conditions, as well as to the development of cells and equipment for the coupling of techniques as IR‐thermogravimetry, IR‐Raman and Raman‐UV‐RPE . The achievement of IR operando cells that can reach temperature up to 1073 K and pressure up to 4 MPa or can allow analysis of catalyst in its industrial form (as deposited on monolith) leads to a development of the applications fields. Moreover, the high sensitivity, good time resolution, easy implementation make these spectroscopies largely used in refining, fine chemistry or pollution abatement…”
Section: Figurementioning
confidence: 99%